Employee Inspiration in Retailing: Opportunities and Risks - Thomas Rudolph; Kathrin Neumüller; Kristina Kleinlercher (Marketing Review St.Gallen, 2021)
Employees' subjective experience of inspiration has attracted only limited attention from marketing and retailing scholars and practitioners. Research in social psychology shows that feeling inspired leads to many positive outcomes. Thus, a stronger focus on inspiring employees may help retailers face current challenges. This article explores how frequently and deeply employees experience inspiration at work and examines the opportunities and risks for retailers. As a result, the authors offer a practical guide on how to inspire employees.
Keywords: 650